Effect Marketing Mix on Purchasing Decision at Small Business Product Using C2C E-Commerce - Permatasari, Dessy; Hildayanti, Siti Komariah (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the impact of product, price, promotion, location, people, physical proof, and method, or what’s known as the 7P marketing mix on Palembang’s character buns purchasing decisions. Multiple linear regression analysis techniques were employed in this study. The population has been the client of the three Bakpao Characters online shops in Palembang City. There were with 110 respondents including Kingsbao, Baperpao and Karapao Palembang. Data were analyzed in this research using version 24 of SPSS. Partially there are 5 variables that have a major impact on the purchasing decision of character buns, namely variables for price, promotion, location, physical proof, and operation. And 2 factors, namely Commodity and Individuals, which have no effect on buying decisions. 2) Around the same time the findings showed that the marketing mix together had an impact on the buying decision on the character of the city of Palembang. In part, price, advertising, location, physical proof, and method are the marketing mix variables that influenced purchasing decisions of Palembang’s Bakpao characters. The factors of the company and the people did not affect purchase decisions. The commodity, price, promotion, location, people, physical evidence and process variables had a simultaneous positive and significant impact on the purchasing decision of the character of Palembang City Bakpao with an F value of 34,066 and a r2 value of 0,700 or 70%.